Eco-Sufism-Based Environmental Education in Islamic Boarding School - Nurjanah, Eneng Sinta; Saputro, Ragil Wahyu; Asyhari, Asyhari; Dewantara, Sastra; Zuhri, Zuhri; Ayob, Noorseha (EDUKASIA, 2026)
Studies on environmental education in pesantren have generally emphasized ecological programs and the integration of Islamic values, but they have not sufficiently explained how Sufistic values are institutionalized to address practical ecological problems such as waste management, water and energy use, greening, and students’ inconsistent environmental discipline. This study aimed to analyze eco-sufism-based environmental education by examining the integration of eco-sufism values in students’ daily ecological activities, the formation of cosmic consciousness through nature tadabbur, the implementation of Sufistic values in pesantren learning and culture, the role of pesantren as a socio-ecological agent, and the formation of students’ ecological identity. This research employed a qualitative case study through participatory observation, semi-structured interviews, and documentation involving pesantren leaders, teachers, administrators, and students. The findings showed that eco-sufism is internalized through zuhud, gratitude, rahmah, amanah, khalifah, and tafakkur in fiqh and moral education, teacher modeling, cleanliness duties, plant care, water and energy conservation, waste discipline, community service, and nature tadabbur. The study concludes that eco-sufism strengthens students’ ecological awareness, discipline, responsibility, cosmic consciousness, and ecological identity. Its contribution lies in offering a pesantren-based environmental education model integrating Islamic spirituality, ecological habituation, and sustainable institutional governance.